(untitled) (Research, Society and Development, 2023)
The objective of the present study is to verify the suspicion of common mental disorders in precarious nursing workers and the association with sociodemographic and occupational characteristics. Method: cross-sectional study carried out in 2020 with 80 precarious nursing workers from a public hospital located in the southeast region of Brazil. In data collection, an instrument containing sociodemographic and occupational variables was used and the Self Report Questionnaire-20 was used to verify common mental disorders. A significance level of 5% was adopted, and the association with sociodemographic and occupational variables was determined through logistic regression using the Chi-square Test – Pearson and Fisher’s Exact. Project approved by the Ethics Committee. Results: the prevalence of common mental disorders in the sample was 52.5%, with an association identified for sex (p= 0.031) and income (p= 0.009). Conclusion: due to the high prevalence of common mental disorders in the sample and the association with gender and income, there is a need for an institutional policy of deprecarious employment with a view to protecting and promoting workers’ mental health.